Linkages between cover crops, phosphorus fertilizer management, soil health, and phosphorus bioavailability in replicated research watersheds - Starr, Laura Marie (Kansas State University, 2020)
Phosphorus (P) pollution from agricultural remains a persistent and complex problem that negatively affects freshwater quality, causing harmful algal blooms and eutrophication. Phosphorus can be lost from fields as sediment bound solids and dissolved in leachate or runoff. Phosphorus is cycled through the soil ecosystem via biotic and abiotic interactions as organic or inorganic compounds. Conservation practices such as no-till and cover cropping have been promoted as ways to promote soil health and reduce sediment loss from cropping systems. A growing body of research has documented increased dissolved reactive P in runoff from cover crops. It is not clear how conservation management interacts with P fertilizer management, nor what their impact is on the biogeochemical cycling of P and its potential for loss. The objective of this study was to document the impact of cover crops and P fertilizer management on P bioavailability and stratification, as well as investigate changing nutrient status on microbial biomass P (MB-P) and the activity of P cycling enzymes. In 2014, a field scale experiment was established in a no-till, corn-soybean cropping system, at the Kansas Agricultural Watershed in NE Kansas. The experiment was organized as a 2*3 full factorial with eighteen, 0.5 ha watersheds, in a randomized complete block design. A cover crop treatment consisted of cover crop (CC) or no cover crop (NC), was implemented with three P fertilizer management treatments; fall surface broadcast diammonium phosphate (FB), spring subsurface injected ammonium polyphosphate (SI), or no P fertilizer (NP). The first objective was accomplished by measuring the gross P pools such as total P (P[subscript]T), and total organic P (P[subscript]O), as well as bioavailable P pools such as water extractable P (P[subscript]W), and 2 mM citric acid extractable P (P[subscript]C), at the 0-5 cm depth (spring/fall 2018 and 2019), and 5-10/10-15 cm depths (fall 2018, and spring/fall 2019). Additionally, we used diffusive gradient thin films (P[subscript]DGT) to measured total soil-water available P, and Mehlich-III (P[subscript]M) to measure the agronomically relevant P, at the 0-5 cm depth (spring/fall 2018 and 2019). The second objective was addressed by measuring MB-P, and P cycling enzyme activity (acid and alkaline phosphatase, and phosphodiesterase) at the 0-5 cm depth, in fall 2018 and spring/fall 2019. We documented P stratification of P[subscript]T in all treatments in fall 2018 and spring 2019, but reduced stratification in NP, and increased stratification in FB and SI by fall 2019. Total organic P was highest in the 5-10 cm depth in FB and SI in spring/fall 2019. While NP treatments almost always had less P than the fertilized treatments, it had either the same or more P[subscript]O than FB and SI. The labile pools of P, P[subscript]W and P[subscript]C, were stratified in FB*CC, FB*NC, SI*CC treatments but not in SI*NC, NP*NC, NP*CC in spring 2019 (P[subscript]W) and fall 2018 and spring 2019 (P[subscript]C). There were cover crop*P fertilizer interactions in the 0-5 cm depth where a SI*CC increased the amount of P compared to SI*NC in P[subscript]W (spring 2019), P[subscript]C (fall 2018 and spring 2019), and P[subscript]DGT (spring 2019). Cover crops did not affect the amount of P[subscript]W, P[subscript]C, P[subscript]DGT, or P[subscript]M in the 0-5 cm depth of NP or FB fertilizer management at any time. Cover crops reduced the amount of P[subscript]C at 5-10 cm (fall 2018 and spring 2019) and P[subscript]DGT at 10-15 cm (fall 2019). Almost identical P fertilizer * cover crop interactions from P[subscript]C and P[subscript]DGT was detected in MB-P in spring/fall 2019. Cover crops consistently increased P cycling enzyme activity compared to NC treatments. The MB-P was higher in fertilized plots compared to NP treatments in all seasons. Low MB-C:P in NP treatments suggest conditions for P immobilization by microorganisms, possibly contributing to organic P pools. These results suggest that cover crops could be translocating P in spring subsurface applied ammonium polyphosphate, that was then being stored in labile P pools, such as MB-P. At the same time, cover crops may be increasing the potential for organic P mineralization in all fertilizer management treatments. This body of research demonstrates that cover cropping and P fertilizer management in no-till corn-soybean cropping systems interact, changing where and how P is stored and cycled. Further research will be necessary to develop more nuanced management recommendations to optimize soil fertility and reduce P loss to runoff.
Keywords: Phosphorus; Cover crops; No-till; Microbial biomass P; Phosphatase enzyme activity